Efek Kualitas Integrated Reporting Terhadap Biaya Modal Ekuitas Yang Dimoderasi Dengan Kompleksitas Organisasi - Amanda Galuh Pitaloka; Ika Permatasari (Liquidity, 2025)
This study aims to obtain empirical evidence regarding the effect of Integrated Reporting (IR) quality on the cost of equity capital, with organizational complexity as a moderating variable. This research sample includes all companies listed on the Indonesia Stock Exchange ESG index consisting of ESGLEADERS, ESGSKEHATI, and ESGQKEHATI. This research was conducted during the period 2019 to 2023 with a total of 117 observations. The method used is multiple linear regression analysis with the Moderated Regression Analysis (MRA) approach. The results showed that IR quality had no effect on the cost of equity capital, and organizational complexity did not moderate the relationship. This is due to several factors, including the limitations of measuring organizational complexity which is only represented by leverage, the observation period which includes disruptions due to the COVID-19 pandemic, and the relatively limited number and diversity of samples. In addition, the utilization of IR information by domestic investors is still low, due to market orientation that still focuses on conventional financial information and short-term performance. The absence of regulations that require the implementation of IR and the inconsistency of disclosure quality between companies are also factors that hinder IR in functioning as a signal of reducing information asymmetry. This study has implications for investors and policies that support the standardization of integrated reporting, so that IR can function optimally in reducing the cost of capital and increasing market efficiency.